Wartime images, peacetime wounds : the media and the Gustafsen Lake standoff - Lambertus, Sandra (Book collections on Project MUSE., 2004)
"In Wartime Images, Peacetime Wounds, Sandra Lambertus asks this question of the media coverage of the largest RCMP operation in Canadian history - the 1995 Gustafsen Lake standoff." "Drawing from extensive newspaper, television, and radio news coverage, legal and law enforcement documents, and ethnographic interviews with journalists, RCMP officers, and Native leaders, Lambertus examines the construction and dissemination of vilifying stereotyped portrayals of Native people. Employing a variety of methodologies including discourse analysis, the investigation shows how the values and perspectives of local communities, media, and law enforcement became overshadowed by those of 'outsiders' during the course of the event. The study culminates with an assessment of the structural elements that contributed to the damaging media portrayals. Provocative and convincingly argued, Wartime Images, Peacetime Wounds opens new avenues for the study of the representation of minorities in the news and for the study of news media in general."--Jacket